2019
DOI: 10.1177/1049909119850807
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Benefits of Palmitoylethanolamide in Palliation: A Qualitative Systematic Review

Abstract: Palmitoylethanolamide (PEA) is a nutraceutical endocannabinoid that was retrospectively discovered in egg yolks. Feeding poor children with known streptococcal infections prevented rheumatic fever. Subsequently, it was found to alter the course of influenza. Unfortunately, there is little known about its pharmacokinetics. Palmitoylethanolamide targets nonclassical cannabinoid receptors rather than CB1 and CB2 receptors. Palmitoylethanolamide will only indirectly activate classical cannabinoid receptors by an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 215 publications
(261 reference statements)
1
23
0
Order By: Relevance
“…In addition, this survey found that nearly all respondents were unfamiliar with PEA, which is an endogenous cannabinoid classified as a nutraceutical, or a food that has potential health or medicinal benefits. 29 PEA has activity at both CB 1 and CB 2 receptors, although it is not itself a component of cannabis 29 and possesses anti-inflammatory effects. 30 - 32 Therefore, the endocannabinoid system could be positively manipulated via PEA without negotiating the legal restrictions surrounding cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this survey found that nearly all respondents were unfamiliar with PEA, which is an endogenous cannabinoid classified as a nutraceutical, or a food that has potential health or medicinal benefits. 29 PEA has activity at both CB 1 and CB 2 receptors, although it is not itself a component of cannabis 29 and possesses anti-inflammatory effects. 30 - 32 Therefore, the endocannabinoid system could be positively manipulated via PEA without negotiating the legal restrictions surrounding cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that very little is known about the pharmacokinetics of PEA in humans ( please see Pharmacokinetic). In fact, the bioavailability and apparent volume of distribution have not been clearly evaluated; and blood PEA levels, at least in animals, do not accurately reflect levels in the CNS (Davis et al, 2019). The micronized or ultramicronized forms of PEA increased bioavailability in animals compared with naïve forms, but there are very few and very recent clinical data to confirm that this is true for humans.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Additionally, PEA is known for its "entourage effect" on the endocannabinoid system (ECS), being able to potentiate the effect of prototypical endocannabinoids, but not carrying their potential side effects (Davis et al, 2019). Interestingly, the non-psychotropic cannabinoid cannabidiol (CBD) was able to prevent the cytotoxic damage caused by TcdA in vitro cultured Caco-2 cells (Gigli et al, 2017).…”
Section: Discussionmentioning
confidence: 99%